Addressing psychiatric disorders and genetics: the meaningful use of comics for health information. (3rd July 2022) - Paixão Pequeno, Daniel; Pequeno Galvão, Lucas; Lourenço, Gustavo Jacob
Abstract: In the fields of healthcare and education, comics have shown considerable academic and teaching importance, with their combination of text and images. As a well-known character in comics, Batman allows us to discuss several relevant topics, from the outcomes in adulthood of experiencing parental death in childhood to genetic and epigenetic changes that may be factors of vulnerability to psychiatric disorders in adulthood. In this text, a narrative of Batman is developed, demonstrating the possibility of using it in an academic context and intending at paying greater attention to patients' history and the relationship between genetics and behaviour.